Socio-Demographic Characteristics of the Bidayuh Respondents and their Impact on the Utilization of Zingiberaceae Plants - Jovita Elderson, Ripen; Meekiong, Kalu; Gabriel Tonga, Noweg (Scope, 2024)
The Bidayuh community in Jagoi and SingaiBau Districts possesses extensive traditional knowledge of Zingiberaceae species. This study documents their uses and examines socio-demographic factors influencing utilization. Gender, age, occupation, income, and religious beliefs significantly impact plant use. Older generations, with their rich traditional knowledge, frequently use medicinal gingers. Women influence plant use in culinary and medicinal practices. The economic status affects the ability to afford these plants. Data from 170 households were collected through structured questionnaires. Pearson correlation and ANOVA analyses were conducted to understand relationships between socio-demographic factors and plant utilization. The results showed a significant positive correlation between age and medicinal ginger use frequency. Additionally, village location impacts collection habits, with Singai residents collecting more frequently. The study underscores the importance of documenting traditional biodiversity conservation and cultural heritage preservation knowledge. Keywords: Ethnobotany, Zingiberaceae, Bidayuh community, Traditional medicine, Socio-demographic factors